Seeds of change: The impact of Ethiopia’s direct seed marketing approach on smallholders’ seed purchases and productivity - Mekonnen, Dawit Kelemework; Abate, Gashaw T.; Yimam, Seid; Benfica, Rui; Spielman, David J.; Place, Frank (World Bank, 2025)
Several factors contribute to the limited use of improved seed varieties in Ethiopia. Among those, on the supply side, is the restricted availability of seeds in the volume, quality, and timeliness required by farmers, partly due to inadequate public and private investment in the sector. Beginning in 2011, the Government of Ethiopia introduced a novel experiment—the direct seed marketing approach—to reduce some of the centralized, state-run attributes of the country’s seed market and rationalize the use of public resources. Direct seed marketing was designed to incentivize private and public seed producers to sell directly to farmers rather than through the state apparatus. This study is the first quantitative evaluation of the impact of direct seed marketing on indicators of a healthy seed system: access to quality seeds and farm-level productivity. Using a quasi-experimental difference-in-differences approach suitable to handling variation in treatment timing, the study finds that direct seed marketing led to an increase of 15 percentage points in the proportion of farmers purchasing maize seed, an increase of 45 percent in the quantity of maize seed purchased per hectare, and an increase of 18 percent in maize yield. However, there are differences across crops, with the effects of direct seed marketing on wheat seed purchases and yields being statistically insignificant. These crop-specific differences in performance are likely explained by differences in the reproductive biology of maize (particularly maize hybrids) and wheat, which tend to incentivize commercial activity in hybrid maize seed markets more than in self-pollinating wheat or open-pollinated maize markets. These differences suggest a need for nuanced policy responses, institutional arrangements, and market development strategies to accelerate the adoption of improved varieties.